The worm hunters [videorecording (DVD)]. - Sherlock, Emma (Green Planet Films, 2012)
In a Turkish headquarters the world's top earthworm scientists concoct a plan to find and name their ultimate discovery. Nothing will stop them as they travel to all corners of the world with spades, GPS worm locators and secret worm outing fluids to unearth their prize. But love turns savage when things don't go to plan and the worm gets the upper hand. An epic adventure into an underground science and an unstoppable passion.